Review Artikel: Terapi Tanaman Herbal Untuk Peningkatan Kadar Hemoglobin - Nisrina Fauziyah Sholihah (Peneliti.net, 2022)
A condition when the body lacks blood cells that contain high levels of hemoglobin is often referred to as anemia. Hemoglobin is a protein in erythrocytes that binds oxygen, CO2, and protons. The body cannot work properly and can be harmful to health if the oxygen intake in the body is below normal limits. Due to the lack of public awareness in consuming Fe tablets, other additional intakes are needed as an alternative to help the formation of hemoglobin in the body. Therefore, the purpose of this literature review is to provide information about herbal plant therapy for increasing hemoglobin levels in the blood. The method of writing this article is a literature review taken from a national journal and true experiment from the last 10 years at Google Scholar and screened with inclusion criteria. Of the various descriptions of plants that have the effect of increasing hemoglobin levels, the results of the highest increase are found in Moringa leaf soup plant products. The increase after consuming Moringa leaf soup reached 2,752 g/dl. This is because Moringa leaves contain high iron, and contain many other minerals, so that the hemoglobin level produced is also higher.